Isolation of Chemical Compounds of Astragalus galactites from Mongolia - Sugarjav, E.; Gunbilig, D.; Irekhbayar, J.; Chimedragchaa, Ch (Asian Journal of Chemistry, 2025)
We present and discuss our recent findings on the chemical analysis of Astragalus galactites (Pall.), a celebrated plant in traditional Mongolian medicine. We aimed to advance the analytical approach to yield precise identification needed for developing new drugs and standardization of active principles and this is the first effort at untargeted metabolite profiling of A. galactites in various plant organs (aerial parts, leaves, roots and flowers) as well as previously isolated fractions of chloroform extract using GC-MS/MS and UPC2-QTOF-MS instruments. Twenty-one compounds, including eight phenolic acid derivatives, seven flavonoids, two diterpenoids derivatives, two monoterpenoids, one sesquiterpenoid, two fatty acids and a lignan were identified by UPC2-QTOF-MS in the chloroform fraction of A. galactites. Further 16 compounds, which are monosaccharide derivatives and alkaloids were successfully identified by GC-MS/MS analysis in the extract of leaves, flowers, roots and aerial parts of A. galactites. Quantification of caffeic acid (7.17 ± 0.003 mg/mL), chlorogenic acid (0.69 ± 0.01 mg/mL) and gallic acid (8.06 ± 0.004 mg/mL) in A. galactites was achieved using a conventional HPLC instrument and a corresponding method validated by acceptable precision (RSD < 2%) and good accuracy (98.7-102.7%, RSD 1.15-1.98%). The presence of the above-mentioned compounds supports the pharmacological effects and radical scavenging activities as reported previously.